Literacy and women empowerment for sustainable development in Nigeria - Abu Samah, Asnarulkhadi; Ndaeji, Muhammad Ndas (Marsland Press, 2013)
This paper examines the role of literacy education as a catalyst for women empowerment in Nigeria for sustainable development. Available records showed that women constituted more than fifty percent of Nigerian population and for any sustainable development in Nigeria to be achieved this greater percentage of the population need literacy and education for income generation skills and vocational training. The general aim of the paper is to describe how literacy education can play a vital role in women’s empowerment, which will in turn lead to sustainable development.